A Development of Sensor Aids for Goalkeeping Violations Over the Goal Line on First Point Penalty Kicks on Futsal - Permana, Yudi; Soegiyanto, Soegiyanto; Kusuma, Donny Wira Yudha (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Futsal game performance is strongly supported by the basic skills possessed by the players, futsal players must have good skills in some basic techniques. Goalkeeper is to minimize the opportunity of the opponent to score against his goal by using the right techniques and tactics, namely by catching the ball, blocking the ball, kicking the ball, and positioning the prime position. The results of observations that have been made by researchers, namely using observes and interviews with goalkeepers, referees and futsal coaches obtained conclusions stating that no tool can help the referee at the time of the first point penalty kick on futsal. The subjects of research are futsal goalkeepers academic futsal Cirebon and the referee asked Cirebon regency who already have a national referee license The result of this study is to produce a sensor tool product to detect the violation of the goalkeeper across the goal line on the first point penalty kick on futsal. result validation expert sensor, futsal and referee Dengan average scoreofeluruhan are